PENGARUH KUALITAS PRODUK, PENETAPAN HARGA, DAN LOKASI USAHA TERHADAP KINERJA USAHA WARUNG ANGKRINGAN DI WILAYAH KECAMATAN PINANG KOTA TANGERANG - Subagia, Dodi; Supriadi , Yudi Nur (Bussman Journal : Indonesian Journal of Business and Management, 2021)
The research sample was 50 respondents who were taken from the owner of the angkringan stalls. The results of the study resulted in a conclusion that there was a significant effect on product quality on business performance, there was a significant effect of price fixing on business performance, there was a significant influence on location on business performance and there was a joint influence on product quality, pricing and business location on micro-business performance. small and medium enterprises in Tangerang City. The location of the business has an influence on business performance, therefore it is recommended that the owner of an angkringan business in determining the location of the business can pay attention to environmental factors around the business location such as the condition of the community around the business location, the comfort and safety of the business place, and easy access to buyers. The results showed that there are still other factors that can affect the performance of the angkringan stalls besides product quality, pricing and business locations, therefore it is recommended that the owners of the angkringan stalls conduct a survey directly to buyers regarding the assessment of consumer satisfaction with product quality, product prices and business location based on buyers' perceptions so that owners of angkringan stalls can make strategies to improve their business according to the characteristics of buyers who are their target market.